2011
DOI: 10.4172/2157-7064.1000105
|View full text |Cite
|
Sign up to set email alerts
|

A Simple HPLC Method for the Separation of Colistimethate Sodium and Colistin Sulphate

Abstract: In this paper, a simple high performance liquid chromatography (HPLC) method for the determination of colistimethate sodium in the productions of synthesis from colistin E sulphate was established. A HPLC gradient which was: 20% B+80% A changed to 50% B+50% A in 10 min (A was 0.05% TFA aqueous solution and B was acetonitrile) was used and the separation was realized in 8 minutes. Moreover, this method was also used in the separation of colistin sulphate with good resolution. Compared to the methods reported pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 11 publications
0
13
0
Order By: Relevance
“…Other studies using HPLC in tandem with this FTIR method can also prove to be powerful strategies for elucidating the chemistry of this complicated prodrug (36,37). For instance, HPLC separation of methanesulfonated colistin A and B products using a method such as that described by Bai et al (10) followed by FTIR analysis can indicate whether one component is more heavily methanesulfonated. Time course studies may determine whether the methanesulfonate is a more labile leaving group on one component or the other.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies using HPLC in tandem with this FTIR method can also prove to be powerful strategies for elucidating the chemistry of this complicated prodrug (36,37). For instance, HPLC separation of methanesulfonated colistin A and B products using a method such as that described by Bai et al (10) followed by FTIR analysis can indicate whether one component is more heavily methanesulfonated. Time course studies may determine whether the methanesulfonate is a more labile leaving group on one component or the other.…”
Section: Discussionmentioning
confidence: 99%
“…High-performance liquid chromatography (HPLC) with UV detection can be used to detect CMS but only at concentrations (0.5 to 5 mg/ml) above those expected in plasma after administration according to current dosing recommendations (9,10). Recently, Nation and colleagues (5,(11)(12)(13) developed an HPLCfluorescence method that enables detection at the physiologically relevant level (0.5 to 30 g/ml) (4,14,15).…”
mentioning
confidence: 99%
“…15 Assay of colistin was conducted via a modified HPLC method originally described by Bai et al 39 with Zorbax SB C-18 column (4.6 Â 150 mm 2 , 3.5 mm; Agilent Technologies) as the stationary phase. The mobile phase consisted of 0.05% (v/v) trifluoroacetic aqueous solution (solvent A) and acetonitrile (solvent B), delivered at 1 mL/min under a linear gradient: 0-8 min, 80%-64% A; 8-10 min, 64% A-80% A. Colistin peak appeared at a retention time of 5.3 min under a UV wavelength of 214 nm.…”
Section: Drug Content Quantificationmentioning
confidence: 99%
“…The large number of components in a CMS solution and their rapid hydrolysis means that, to the best of our knowledge, there are no HPLC methods reported that directly quantify CMS. The HPLC methods for CMS that are published are either for the separation of CMS [4] or require the hydrolysis of CMS to colistin, which is then quantitated [3,5,6,7]. The methods of hydrolysing CMS to colistin can be complex and time-consuming and rely on the assumption that all of the CMS components have fully hydrolysed to colistin without the degradation of any of the colistin in the sample during that time period.…”
Section: Introductionmentioning
confidence: 99%